Simultaneous versus staged resection for synchronous colorectal liver metastases: A population-based cohort study. (February 2020) - Bogach, Jessica; Wang, Julian; Griffiths, Christopher; Parpia, Sameer; Saskin, Refik; Hallet, Julie; Ruo, Leyo; Simunovic, Marko; Serrano, Pablo E.
Abstract: Background: Synchronous liver metastases from colorectal cancer may be resected simultaneously with the primary or as a second staged operation. We evaluated trends of resection for synchronous colorectal cancer liver metastases and associated patient outcomes. Methods: This is a retrospective cohort study that included patients undergoing resection for synchronous colorectal cancer liver metastases from 2006 to 2015 in the province of Ontario, Canada (population 13 million). Simultaneous resections occurred on the same admission, while staged resections occurred less than 6 months apart. Outcomes included postoperative complications, length of hospital stay, and overall survival. Kaplan Meier survival estimates, Cox proportional hazard models and logistic regression were used. Results: Among 2, 738 patients undergoing resection for colorectal cancer liver metastases, 1168 (42%) had synchronous disease. Of these, 442 resections were simultaneous (38%) and 776 were staged (62%). The proportion of synchronous disease among patients undergoing resection increased on average 3% per year (p = 0.02). For simultaneous versus staged resection, respectively, median length of hospital stay was shorter (8 vs. 11 days, p < 0.001); rate of major liver resections was lower (17% vs. 65%, p < 0.001), major postoperative complications were similar (28% vs. 23%, p = 0.067), and 90-day post-operative mortality was higher (6% vs. 1%, p < 0.001). Chemotherapy was administered more commonly among patients undergoing staged resections (91% vs. 76%, p < 0.001). Simultaneous resection was associated with a lower median overall survival (40 months, 95%CI 35–46 vs. 78 months, 95%CI 59–86). Risk factors for lower survival included higher comorbidities, right-sided primary and simultaneous resection. Conclusion: Simultaneous resection was associated with similar postoperative complications, higher postoperative mortality and poorer long-term survival. Prospective randomized trials can inform the role of simultaneous versus staged resection for synchronous colorectal cancer liver metastases. Highlights: The proportion of synchronous colorectal cancer liver metastases is increasing. 40% of these patients with synchronous disease undergo simultaneous resection. Simultaneous resection has a shorter length of stay and a similar complication rate.